2018
DOI: 10.1088/1361-6455/aac3c0
|View full text |Cite
|
Sign up to set email alerts
|

Correlative microscopy of morphology and luminescence of Cu porphyrin aggregates

Abstract: Transfer of energy and information through molecule aggregates requires as one important building block anisotropic, cable-like structures. Knowledge on the spatial correlation of luminescence and morphology represents a prerequisite in the understanding of internal processes and will be important for architecting suitable landscapes. In this context we study the morphology, fluorescence and phosphorescence of molecule aggregate structures on surfaces in a spatially correlative way. We consider as two morpholo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Owing to forbidden transition between the FES (i.e., T 1 state for a closed‐shell system) and the GS (i.e., S 0 state for a closed‐shell system), there would be a long‐life FES for porphyrins and the derived MOFs 22 . Moreover, the porphyrin aggregates like MOFs would have more abundant stable FESs due to the increased probabilities of radiationless transitions 23,24 . The phosphor decay profiles of the solid PCN‐H and PCN‐ M s tested at ambient temperature demonstrate that the effective lifetimes of their FESs averagely persist for more than 40 μs (Figure 1C,D), 25–27 which is durable enough to meet the molecular adsorption equilibrium over the modulated ASs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to forbidden transition between the FES (i.e., T 1 state for a closed‐shell system) and the GS (i.e., S 0 state for a closed‐shell system), there would be a long‐life FES for porphyrins and the derived MOFs 22 . Moreover, the porphyrin aggregates like MOFs would have more abundant stable FESs due to the increased probabilities of radiationless transitions 23,24 . The phosphor decay profiles of the solid PCN‐H and PCN‐ M s tested at ambient temperature demonstrate that the effective lifetimes of their FESs averagely persist for more than 40 μs (Figure 1C,D), 25–27 which is durable enough to meet the molecular adsorption equilibrium over the modulated ASs.…”
Section: Resultsmentioning
confidence: 99%
“…22 Moreover, the porphyrin aggregates like MOFs would have more abundant stable FESs due to the increased probabilities of radiationless transitions. 23,24 The phosphor decay profiles of the solid PCN-H and PCN-Ms tested at ambient temperature demonstrate that the effective lifetimes of their FESs averagely persist for more than 40 μs (Figure 1C,D), [25][26][27] which is durable enough to meet the molecular adsorption equilibrium over the modulated ASs. This means that, once the external excited light source is continuous, abundant FES-modulated ASs should emerge and work, and the in situ application of the FESs must be possible.…”
Section: Relatively Static Excited Statesmentioning
confidence: 98%
“…It has been reported that complex porphyrin architectures comprise simpler ones, resulting from the side-by-side or face-to-face positioning of the molecules [ 50 ]. In the case of 3D aggregates—such as the ones observed for this specimen—these two types of assemblies, referred to as J-type and H-type arrangements, are both present [ 51 ].…”
Section: Resultsmentioning
confidence: 99%